Variación de ingresos en la Cooperativa Juan Pio de mora ubicado en Babahoyo de la provincia de los ríos en los periodos 2021 y 2022 - Sánchez Rivera, Priscila Maritza (2023)
The study of income variation at the Juan Pío De Mora Cooperative during the years 2021 and 2022 provides clarity and understanding about significant changes in its financial performance. In this period, the cooperative experienced a noticeable growth in its net interest margins and gross financial margins, indicating an improvement in its ability to generate income from interest and discounts earned in its operations. However, there was a decrease in profit before taxes and profit or loss for the year as a percentage of total income, suggesting less favorable financial performance in 2022 compared to the previous year. This analysis highlights the need to focus on operational efficiency and diversify sources of income to ensure long-term financial stability for the cooperative. It is essential for the Juan Pío De Mora Cooperative to implement strategies that maintain a balance between profit margins and operating costs while exploring opportunities to expand its financial services and products. These measures are key to ensuring a solid and sustainable financial future in the competitive cooperative and banking environment.